Cytoprotective Effect of Pteryxin on Insulinoma MIN6 Cells Due to Antioxidant Enzymes Expression via Nrf2/ARE Activation - Junsei Taira; Ryuji Tsuda; Chika Miyagi-Shiohira; Hirofumi Noguchi; Takayuki Ogi (MDPI AG, 2023)
The low-level antioxidant activity of pancreatic islets causes type 1 diabetes due to oxidative stress, which is also the cause of failure in the pancreatic islets' isolation and cell transplantation. In our previous study, pteryxin was found to be a natural product as a nuclear factor-erythroid-2-related factor (Nrf2) activator. This study focused on elucidation that the potentiality of pteryxin can activate the antioxidant enzymes, even under oxidative stress, by hydrogen peroxide (H2O2). Pteryxin treated with mouse insulinoma MIN6 cells was enhanced the antioxidant gene expressions in the ARE (antioxidant response element) region for HO-1 (Heme Oxygenase-1), GCLC (Glutamate-cysteine ligase catalytic subunit), SOD1 (Super Oxide dismutase1), and Trxr1 (Thioredoxin reductase1), and those enzymes were also expressed during the nuclei transference of cytoplasmic Nrf2. In fact, the cells exposed to H2O2 concentrations of a half-cell lethal in the presence of pteryxin were then induced main antioxidant enzymes, HO-1, GCLC, and Trxr1 in the ARE region. The increased glutathione (GSH) levels associated with the GCLC expression also suggested to be cytoprotective against oxidative stress by activating the redox-metabolizing enzymes involving their increased antioxidant activity in the cells. In addition, Akt is a modulator for Nrf2, which may be responsible for the Nrf2 activation. These results allowed us to consider whether pteryxin or its synthesized congeners, an Nrf2 activator, is a potential preservative agent against islet isolation during cell transplantation.